NPI Effectiveness on COVID-19 Infections and its Impact on Economy - Aditya Harin Nugroho; Dewa Gede Karma Wisana (Economics Development Analysis Journal, 2025)
This paper assesses the effectiveness of movement restriction policies in Indonesia (Non-Pharmaceutical Interventions, NPIs) in controlling COVID-19 transmission and their implications for regional economic performance. By integrating an epidemiological framework with the model of economic growth, this study offers a novel approach to assessing how public health policies interact with economic dynamics at the provincial level in period July 2020 – September 2021. Using district-level data from Kawalcovid19 and MoH, the analysis shows comprehensive restriction packages such as PSBB II and PPKM Level 1-4 were largely ineffective nationwide. In contrast, specific interventions such as stricter school closures, workplace closures, and international travel controls were significantly associated with fewer new cases in Java and Indonesia while did not hinder provincial economic growth. These results underscore the value of targeted, evidence-based measures over broad restrictions. The paper contributes to the literature by bridging epidemiological modeling and economic growth analysis, offering insights for designing pandemic responses that balance health protection and economic stability. The study provides policy insights for managing future pandemics in developing countries with large informal sectors and limited fiscal capacity.